Subdural hemorrhage in a cohort with cerebral sinovenous thrombosis: Application to abusive head trauma. (July 2021) - Anderst, James; Carpenter, Shannon; Frazier, Terra; Appavu, Brian; Noetzel, Michael; Beslow, Lauren A.; Sharma, Mukta; ,
Abstract: Background: Cerebral sinovenous thrombosis (CSVT) is a postulated cause of subdural hemorrhage (SDH) that is hypothesized to mimic abusive head trauma (AHT). Minimal data exists directly investigating this relationship. Objectives: To evaluate the frequency of SDH in children with CSVT, identify factors associated with CSVT and SDH, and to assess if any association supports the hypothesis that CSVT causes SDH. Participants and setting: The International Pediatric Stroke Study (IPSS) prospectively collects data on subjects birth to 19 years of age with intracranial thrombosis. Methods: IPSS subjects with CSVT and SDH were compared to those with CSVT and no SDH. For subjects with CSVT and SDH, neuroimaging reports further characterized the findings. In any case with no known risk factors for SDH, neuroimaging studies were reviewed by a pediatric neuroradiologist. Results: Of 216 subjects with CSVT, 20 (9.3%) had SDH. Those with SDH (median age 0.3 years) were younger than those without SDH (median age 4.2 years), p < 0.001. Subjects with CSVT and SDH more frequently had anoxia (OR = 10.8; 95% CI: 1.4, 81.1), head/neck injury (OR = 4.0; 95% CI: 1.3, 12.6), or abnormal consciousness (OR = 3.0; 95% CI: 1.2, 7.6). Of 20 subjects with CSVT and SDH, 19 had known risk factors for SDH. The remaining subject had a chronic SDH identified concomitantly to a newly symptomatic CSVT with accompanying venous infarctions. Conclusions: SDH in the setting of CSVT is typically identified in children with independent risk factors for SDH. This study does not support the hypothesis that CSVT causes SDH. Highlights: Cerebral sinovenous thrombosis has been hypothesized to cause subdural hemorrhage. This hypothesis is frequently proposed in legal settings involving abusive head trauma. Little data exists evaluating this hypothesis. This study evaluates this hypothesis using a large international database. Results of this study does not support the hypothesis that CSVT causes SDH.